Salt Supply Chain Management at Regional Level: Case Study of Salt Processing Industry and Salt Consumer Industry in Central Java - Siwi Hadi Purnanto; Suadi Suadi; Ustadi Ustadi (Universitas Gadjah Mada, 2020)
The need of salt for industry in Central Java Province is still largely supplied by salt products from other provinces, even though Central Java is one of the major salt-producing provinces in Indonesia. This studyanalyzed supply chain models of salt in selected industry in Central Java.. The study was conducted through case study on two selected industrial groups: (1) the salt processing industry, represented by two salt processing companies and (2) the salt user industry, represented also by two salt users (food and non-food industry), in Central Java. Indepth interview was applied to collect data, included the data on the flow of goods, flow of finances, and flow of information patern. The data was used to finalize the structure and model of salt supply chain in Central Java. The data were analyzed using descriptive qualitative analysis, which refers to SCOR (Supply Chain Operations Reference) model dimension. The study showed that the salt processing industry supplied majorly by out-region supplier, counted for 30 – 70% of raw salt material needed.. The salt processing industry with large storage tended to keep large amount of salt as investment (buffer stock). In addition, industry with smaller storage capacity attempted to enhance the stok utility and accelerated cash-to-cash conversion for the available salt. The salt supply chain model on the processing industry possessed good reliability. In addition, the fish processing and textile industry merely made purchase to local area suppliers. The textile industry applied a collaborative management and took leadership role in the collaborative supply chain to secure the salt supply continuity.